Cyclooxygenase-2 in testes of infertile men: Evidence for the induction of prostaglandin synthesis by interleukin-1β - Matzkin, Maria Eugenia (2010)
As we previously reported, testes of men suffering from hypospermatogenesis and germ cell arrest or Sertoli cell-only syndrome show a major increase in the number of macrophages expressing interleukin-1β (IL-1β) and abundant expression of cyclooxygenase-2 (COX-2), the inducible isoform of the key enzyme in the biosynthesis of prostaglandins (PGs), in Leydig cells. In the present study we report [1] a positive correlation between IL-1β levels and COX-2 expression in testes of infertile patients, [2] the induction of COX-2 by IL-1β in mouse Leydig cells (TM3) and human macrophages (THP-1), and therefore [3] evidence for an IL-1β-dependent induction of testicular inflammatory states.